FRAMEWORK FOR INVESTING INDONESIAN EFL LISTENING MATERIALS WITH CHARACTER EDUCATION - Kusumaningputri, Reni; Khazanah, Dewianti; Setiarini, Riskia (TARBIYA: Journal of Education in Muslim Society, 2017)
Abstract This paper offers a solution to Indonesia’s mission of investing EFL listening materials with character education in higher institutions. The character is seen as a dimension of content competence, namely attitude. Developed by using Content-Based Instruction approach, the alternative view is reflected through listening materials design to target strengthening moral values, principles, and attitudes. The framework argues that listening materials should accommodate the need to tailor materials for teaching, rather, than for assessment. It also responds to the ubiquity of English as a Lingua Franca. It argues that the investment of character education leads to learning targets that allow students to become concerned, informed, and involved in developing themselves as citizens, and to respond to 21st-century language competences, especially in the ability to embrace cross-cultural understanding and in the use of digital technology in classroom language learning. The proposed framework is offered as decisions made on the materials’ resources, method of development, activities, and assessment.   Abstrak Artikel ini menawarkan solusi terhadap misi Indonesia untuk berinvestasi pendidikan karakter di dalam materi ajar Listening untuk pembelajaran di pendidikan tinggi (universitas). Karakter dimaknai sebagai kompetensi isi yaitu perilaku. Rancangan materi ini dikembangkan dengan menggunakan pendekatan berbasis isi (Content-Based Instruction). Kerangka rancangan alternatif ini bertujuan untuk menguatkan nilai-nilai moral, prinsip, dan perilaku. Dengan kerangka berfikir bahwa materi Listening seharusnya dibuat untuk tujuan belajar (learning) daripada untuk asesmen semata-mata, maka materi ajar harus mengakomodasi pola ini. Rancangan materi ini juga merespon kehadiran perspektif English as a Lingua Franca. Hal ini bermakna bahwa investasi pendidikan karakter hendaknya bermuara pada tujuan-tujuan pembelajaran yang menciptakan pembelajar menjadi pribadi yang perhatian, cakap pengetahuan, dan partisipatif dalam mengembangkan dirinya sebagai warga negara. Selain itu rancangan materi ini juga merespon pentingnya tercapainya kompetensi berbahasa abad ke -21 khususnya kemampuan pemahaman lintas budaya dan penggunaan teknologi digital untuk keperluan pembelajaran di dalam kelas. Kerangka rancangan materi ini tercermin pada pemilihan sumber materi, metode pengembangan materi, aktifitas, serta asesmen.  How to Cite : Kusumaningputri, R., Khazanah, D., Setiarini, R. (2017). Framework for Investing Indonesian EFL Listening Materials with Character Education. TARBIYA: Journal of Education in Muslim Society, 4(2), 184-199. doi:10.15408/tjems.v4i2.6197. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v4i2.6197